The Functions of State Institutions: Constitutional Legal Aspect - KRAVTSOVA, Zorina S.; SINKEVYCH, Olena V.; KUDRIAVTSEVA, Olena M. (Journal of Advanced Research in Law and Economics, 2019)
General principles of functioning of state-legal phenomena are an integral element of the constitutional science subject. The urgency of the article topic is determined with the need for further theoretical development of the processes of state institutions’ functioning and studying the degree of effectiveness of their implementation. The novelty of the research lies in the fact that it contains the further development of general theoretical statements about the concept and essence of the functions of state institutions, as well as summarized and systematized multiple approaches to the classification of functions. In general, the authors’ team deepens and develops the methodology of the functional approach to the study of legal phenomena. Practical application of the research results is possible provided that the right of citizens to formulate aspects of activities in the field of functions of state institutions and predetermine their necessity is constitutionally realized. The authors believe that the use of the branch of constitutional law will reflect the interests of the largest part of the population and, in such a way, it will be difficult to change the private order of the basic functions of state institutions.